MicroRNA‐146a downregulates IL‐17 and IL‐35 and inhibits proliferation of human periodontal ligament stem cells. Issue 8 (15th April 2019) - Zhao, Sen; Cheng, Yawei; Kim, Jong Ghee
Abstract: Periodontitis is characterized by increased levels of proinflammatory factors, such as interleukin‐17 (IL‐17) and IL‐35. In this study, the expression of microRNA‐146a (miRNA‐146a), IL‐17, and IL‐35 in the plasma of patients with periodontitis and healthy controls were detected by quantitative reverse transcription polymerase chain reaction and enzyme‐linked immunosorbent assay, respectively. miRNA‐146a mimic was transfected into periodontal ligament stem cells (PDLSCs) isolated from periodontitis‐affected teeth and healthy teeth. Cell proliferation and expression of IL‐17 and IL‐35 were detected by cell counting kit‐8 assay and Western blot analysis, respectively. It was observed that miRNA‐146a was downregulated but IL‐17 and IL‐35 were upregulated in the plasma of patients with periodontitis than in healthy controls. miRNA‐146a was inversely correlated with IL‐17 and IL‐35 in patients with periodontitis. miRNA‐146a overexpression inhibited proliferation of PDLSCs derived from both periodontitis‐affected teeth and healthy teeth. miRNA‐146a overexpression led to downregulated IL‐17 and IL‐35 expression in PDLSCs isolated from periodontitis‐affected teeth. We, therefore, conclude that miRNA‐146a may improve periodontitis by downregulating IL‐17 and IL‐35 expression and inhibiting proliferation of human PDLSCs. Abstract : Periodontitis is characterized by increased levels of proinflammatory factors, such as IL‐17 and IL‐35. In this study, expression of microRNA‐146a (miRNA‐146a), IL‐17, and IL‐35 in the plasma of patients with periodontitis and healthy controls was detected by quantitative reverse transcription polymerase chain reaction and enzyme‐linked immunosorbent assay, respectively. Expression of miRNA‐146a was inversely correlated with the expression of IL‐17 and IL‐35 in patients with periodontitis but not in healthy controls. miRNA‐146a overexpression inhibited proliferation of periodontal ligament stem cells (PDLSCs) derived from both periodontitis‐affected teeth and healthy teeth. miRNA‐146a overexpression led to downregulated IL‐17 and IL‐35 expression in PDLSCs isolated from periodontitis‐affected teeth. We, therefore, conclude that miRNA‐146a may improve periodontitis by downregulating IL‐17 and IL‐35 expression and inhibiting proliferation of human PDLSCs.